Perhitungan matematis qodho’ puasa dengan metode penentuan jumlah hari menurut madzhab Syafi’i - Maryam, Siti; Zah, Yeni Aulia Maharani; Rosyidah, Naili Inayatur; Yaqin, Ainul (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
Ramadan fasting is a fundamental obligation for every Muslim who is mature and of sound mind. However, in practice, there are conditions such as illness, travel, or certain factors that prevent a person from fasting fully. In Shafi'i fiqh, the obligation to make up (qodho') fasting is a must. If the postponement of qodho' lasts until the next Ramadan without a valid excuse, then in addition to the obligation of qodho', fidyah is also added. The problem that arises is the confusion among the community regarding how to calculate the number of qodho' days and the amount of fidyah that must be paid, so a more systematic calculation formula is needed. This study aims to formulate a mathematical calculation for qodho' fasting using the method of determining the number of days according to the Shafi'i school of thought, so that it can be applied practically and remains in accordance with the provisions of fiqh law. The research method uses a literature study with a descriptive-analytical approach. Data was obtained through a search of classical Shafi'i school literature, such as al-Umm by Imam Shafi'i and al-Majmū' by Imam Nawawi, and reinforced with contemporary sources in the form of fatwas from scholars, scientific articles, and guidelines from official religious institutions. The results of the study show that the calculation of qodho' fasting can be formulated in a simple mathematical model, namely the number of days of fasting that are missed multiplied by the total number of Ramadan days that have passed. If the postponement is carried out without a valid reason, then the obligation of fidyah is added according to the number of days postponed. This provides practical clarity for Muslims, minimizes confusion, and strengthens the community's understanding of the balance between fiqh norms and practical needs. In conclusion, the mathematical calculation of qodho' and fidyah according to the Shafi'i school of thought can be an effective educational solution, making it easier for the community to practice the teachings, while bridging classical texts with contemporary contexts.